Heterotopia in Individuals with 22q11.2 Deletion Syndrome - Neuhaus, E.; Hattingen, E.; Breuer, S.; Steidl, E.; Polomac, N.; Rosenow, F.; Rüber, T.; Herrmann, E.; Ecker, C.; Kushan, L.; Lin, A.; Vajdi, A.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: MR imaging studies and neuropathologic findings in individuals with 22q11.2 deletion syndrome show anomalous early brain development. We aimed to retrospectively evaluate cerebral abnormalities, focusing on gray matter heterotopia, and to correlate these with subjects’ neuropsychiatric impairments.MATERIALS AND METHODS: Three raters assessed gray matter heterotopia and other morphologic brain abnormalities on 3D T1WI and T2*WI in 75 individuals with 22q11.2 deletion syndrome (27 females, 15.5 [SD, 7.4] years of age) and 53 controls (24 females, 12.6 [SD, 4.7] years of age). We examined the association among the groups’ most frequent morphologic findings, general cognitive performance, and comorbid neuropsychiatric conditions.RESULTS: Heterotopia in the white matter were the most frequent finding in individuals with 22q11.2 deletion syndrome (n = 29; controls, n = 0; between-group difference, P < .001), followed by cavum septi pellucidi and/or vergae (n = 20; controls, n = 0; P < .001), periventricular cysts (n = 10; controls, n = 0; P = .007), periventricular nodular heterotopia (n = 10; controls, n = 0; P = .007), and polymicrogyria (n = 3; controls, n = 0; P = .3). However, individuals with these morphologic brain abnormalities did not differ significantly from those without them in terms of general cognitive functioning and psychiatric comorbidities.CONCLUSIONS: Taken together, our findings, periventricular nodular heterotopia or heterotopia in the white matter (possibly related to interrupted Arc cells migration), persistent cavum septi pellucidi and/or vergae, and formation of periventricular cysts, give clues to the brain development disorder induced by the 22q11.2 deletion syndrome. There was no evidence that these morphologic findings were associated with differences in psychiatric or cognitive presentation of the 22q11.2 deletion syndrome.ADHDattention deficit/hyperactivity disorderASDautism spectrum disorderCSPcavum septi pellucidiCVcavum vergae22q11.2DS22q11.2 deletion syndromeIQintelligence quotientPNHperiventricular nodular heterotopia